HIGH STRESS HYPERGLYCEMIA RATIO VERSUS ABSOLUTE HYPERGLYCEMIA AS PREDICTOR OF POOR OUTCOME AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS AND MODERATE TO CRITICAL COVID-19 INFECTION ADMITTED AT UNIVERSITY OF SANTO TOMAS HOSPITAL FROM 2020-2021: A RETROSPECTIVE STUDY - Bello, Mary Kenette; Cunanan, Elaine; Mendoza, Erick; Bagos, John Paul Martin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Patients with diabetes are vulnerable and highly susceptible to contracting COVID-19. Stress Hyperglycemia Ratio (SHR) may provide prognostic information in hospitalized patients. It is debatable whether stress hyperglycemia directly leads to poor outcomes or is simply a marker of increased stress and inflammation. This study investigates whether high SHR is associated with poor clinical outcomes among patients with Type 2 Diabetes Mellitus (T2DM) and moderate to critical COVID-19 infection. Moreover, this study aims to compare high SHR versus absolute hyperglycemia as a predictor of poor outcomes. METHODOLOGY A retrospective chart review involving 146 patients with moderate to critical COVID-19 and T2DM was done fromMarch 2020 to December 2021. To determine the SHR level associated with in-hospital mortality, the area under the receiver operating curve was initially conducted to categorize SHR into low and high levels. RESULTS The association of high SHR levels and absolute hyperglycemia with the outcomes (Hypoxemia SpO2 1.082) is associated with poorer outcomes, increased invasive mechanical ventilatory support likelihood, and increased mortality. CONCLUSION The results demonstrated that High SHR could be a better prognostic marker than absolute hyperglycemia.